167P Efficacy of cetuximab based chemotherapy after immunotherapy treatments (IT) in recurrent/metastatic (R/M) head and neck squamous cell carcinoma (HNSCC) patients (pts). (15th December 2019) - Hernando-Calvo, A; Mirallas, O; Marmolejo, D; Felip, E; Garralda, E; Javierre, G Villacampa; Feliu, B; Martínez, S; Gutierrez, R; Dienstmann, R; Braña, I
Abstract: Background: A combination therapy based on chemotherapy (CT) and Anti-PD1 is the new standard FDA-approved first-line treatment for (R/M) HNSCC PD-L1 negative pts. The addition of pembrolizumab to cetuximab has been proved feasible in a recent Phase II trial for anti-PD-1/PD-L1 and cetuximab naïve HNSCC pts. The efficacy of cetuximab-based CT regimens in the post-IT setting, has not been assessed. Methods: We analyzed 27 R/M HNSCC pts treated at the Vall d´Hebron Hospital from 2015-2019 with CT post-IT, including cetuximab-based CT (CT+cetu post-IT) and non-cetuximab CT regimens (CT post-IT). Clinicopathological features and treatment modalities were correlated with outcomes. Overall survival (OS) was calculated from the first cycle of CT post-IT until death or last follow-up with Kaplan-Meier method. Results: Out of 27 pts, median age was 62y, all ECOG ≤1, treated with CT+cetu post-IT 20 pts (74%) or CT post-IT 7 pts (26%). P16 immunohistochemistry was present in 3 pts (17%). Median prior lines was 1 (range 1 - 4) and median follow-up was 6 months (m). Median OS was 8 m (CI95% 5 - 23) and median progression free survival (PFS) 5 m (CI95% 3 - 7). No significant differences were found in OS according to cetuximab addition (P = 0.252 log-rank test). In the CT post-IT cohort, 2 pts (29%) had a partial response (PR) and 5 (71%) had progressive disease. Clinical benefit rate (CBR, defined as complete + partial + stable disease) was 29%. Among pts treated with CT+cetu post-IT, 2 pts (11%) achieved a complete response (CR), 10 (52%) achieved a PR and 2 (11%) stable disease (CBR= 74%). A significantly higher CBR was observed for cetuximab based CT regimens following IT (P = 0.036 chi-square test). Among CR pts in the CT+cetu post-IT cohort, all were cetuximab naïve. Interestingly, both pts achieving a CR had PD as best response on previous IT. Conclusion: In our cohort, the addition of cetuximab to CT post-IT was associated with promising CBR. These results suggest that CT+cetu post-IT regimens may have a role in (R/M) HNSCC pts. Future prospective trials are needed to assess the sensitization effect of IT on cetuximab-based CT and the optimal sequence of treatments in (R/M) HNSCC. Legal entity responsible for the study: Vall d´Hebron Institute of Oncology. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.